The cinema book - Cook, Pam 1943- (London British Film Institute, 1985)
This volume is a guide to understand the movies. Prepared by the British Film Institute and published in Britain, the editor includes information on film history and theory, stars, and "authorship" offers discussion and analysis. Divided into five main sections --- History, Genre, Authorship, History of Narrative, and Narrative and Structuralism --- each is separately authored by writers who argue from their different perspectives on film theory and criticism.
History of the cinema -- Introduction -- American film industry -- Technology -- National cinemas and film movements -- Stars -- Genre -- History of genre criticism -- The Western -- Melodrama -- The gangster/crime film -- The horror film -- The musical -- Authorship and cinema -- Introduction -- Authorship in art cinema -- For a new French cinema: the 'politique des auteurs' -- The auteur theory -- Auteur theory and British cinema -- Structuralism and auteur study -- Auteur study after structuralism -- History of narrative codes -- Introduction -- Early cinema -- The classic narrative system -- Alternative narrative system -- Film narrative and the structuralist controversy -- Introduction -- Bazin -- Metz -- Levi-Straus -- Propp -- Barthes -- Narrative and audience.
Includes bibliographical references, filmography and index.
Keywords: Motion pictures